2014
DOI: 10.1097/aog.0000000000000410
|View full text |Cite
|
Sign up to set email alerts
|

Depression Drug Treatment Outcomes in Pregnancy and the Postpartum Period

Abstract: Evidence about the comparative benefits and harms of pharmacologic treatment of depression in pregnant and postpartum women was largely inadequate to allow informed decisions about treatment. Considering the prevalence of depression, filling this gap is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…However, such a task remains exceedingly difficult, given the paucity of randomized controlled trials of antidepressant use in pregnancy as highlighted by a recent metanalysis on this issue. 41 However, one key aspect of these policy statements is that the recommendations include pharmacotherapy “for depression.” Our analysis suggests that women without depression are also receiving antidepressants. It is possible that women were well-controlled on their medications and thus the providers did not consider them “depressed” and omitted a code for depression.…”
Section: Discussionmentioning
confidence: 99%
“…However, such a task remains exceedingly difficult, given the paucity of randomized controlled trials of antidepressant use in pregnancy as highlighted by a recent metanalysis on this issue. 41 However, one key aspect of these policy statements is that the recommendations include pharmacotherapy “for depression.” Our analysis suggests that women without depression are also receiving antidepressants. It is possible that women were well-controlled on their medications and thus the providers did not consider them “depressed” and omitted a code for depression.…”
Section: Discussionmentioning
confidence: 99%
“…Although several systematic reviews have been completed that report that antidepressants are associated with significant reductions in depressive symptoms in women with unipolar depression postpartum 56, 57 , there is only one published study to date of the acute treatment of acute bipolar postpartum depression 58 . In a chart review of 18 bipolar women who were treated with quietapine alone (or with sedative hypnotic), Sharma et al 58 reported that 83% were much improved or improved on retrospective Clinical Global Impression Scale scores.…”
Section: Part Iv: Recent Advances In Acute Pharmacologic and Psychothmentioning
confidence: 99%
“…Placebo-controlled, randomized trials of antidepressant substances in this population are lacking, and the methodological flaws of available studies limit the generalizability of the findings. A large meta-analysis recently concluded that evidence over benefits/harms of available compounds cannot adequately support informed decisions about the treatment of PND [14]. Furthermore, teratogenicity concerns commonly influence women’s acceptance of potentially effective treatments.…”
Section: Introductionmentioning
confidence: 99%